Laws for expanding access to medications for opioid use disorder: a legal analysis of 16 states & Washington D.C. (4th July 2022) - Andraka-Christou, Barbara; Saloner, Brendan; Gordon, Adam J.; Totaram, Rachel; Randall-Kosich, Olivia; Golan, Matthew; Stein, Bradley D.
ABSTRACT: Background: Medications for opioid use disorder (MOUDs) are the gold standard for OUD treatment but are underused. To our knowledge, no published study has systematically identified and categorized state policy innovations for expanding MOUD utilization. Objective: We sought to identify and categorize state MOUD policy innovations. Methods: Within a stratified random sample of 16 U.S. states and Washington D.C. we searched for 2019 state statutes and regulations related to MOUD in Westlaw legal database. We then identified laws that appeared designed to increase MOUD utilization and categorized them using a template analysis approach. Results: We found 82 laws with one or more MOUD expansion policies. We identified six high-level MOUD expansion policy categories: 1) policies expanding the availability of waivered buprenorphine providers; 2) needs assessments and policies increasing public MOUD awareness; 3) criminal justice system policies; 4) Substance use disorder (SUD) treatment and sober living facility policies; 5) insurance policies; and 6) hospital policies. SUD treatment and housing facility policies, as well as insurance policies, were most common. Conclusions: Multipronged approaches are being pursued by several states to increase MOUD access. Our results can inform policymakers of MOUD expansion approaches in other jurisdictions. Policy categories can serve as the basis for policy variables for future analyses of policy effects.